Composite multi-dimensional nanocatalyst, preparation method and application thereof
Patent Information
- Application Number
- CN202310595981.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-24
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2043-05-24
AI Technical Summary
In existing PEM water electrolysis hydrogen production technology, there are problems such as the high loading of precious metal iridium and low OER activity, especially the insufficient mass transfer efficiency and conductivity at the three-phase interface, which affect the catalytic efficiency.
A composite multidimensional nanocatalyst, comprising an IrOx core-shell structure and a nanotubular polyaniline conductive polymer support, was prepared by wet chemical and electrochemical oxidation methods. This method avoids the influence of temperature, improves electron and ion conduction, disperses the nano-noble metal catalyst, and enhances the activity of the three-phase interface.
It improves OER activity, enhances catalyst mass transfer efficiency and conductivity, reduces the amount of precious metals used, adapts to the low pH environment of water electrolysis for hydrogen production, and improves the catalyst's specific activity and acid corrosion resistance.
Smart Images

Figure CN116695139B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of catalyst technology for hydrogen production through water electrolysis, and specifically relates to a composite multidimensional nanocatalyst, its preparation method, and its application. Background Technology
[0002] Renewable energy coupled with water electrolysis for hydrogen production is a major method for producing green hydrogen energy. Among these methods, proton exchange membrane (PEM) water electrolysis technology, using a proton exchange membrane as the electrolyte, can shorten the distance between the anode and cathode compared to alkaline water electrolysis, thus reducing ohmic polarization of the electrolyzer during operation. Simultaneously, the proton exchange membrane's good selective permeability reduces cross-contamination between hydrogen and oxygen. Therefore, PEM water electrolysis technology offers advantages such as higher current density, wider load range, faster dynamic response (less than 5 seconds), high safety, and non-corrosive feedstock, making it better suited for renewable energy and fully leveraging the technological advantages of water electrolysis for hydrogen production in conjunction with renewable energy sources.
[0003] Currently, PEM (Potential Electrolysis) water electrolysis technology still falls short of meeting the demands for green hydrogen production. The technical challenges are as follows: 1. Reducing the high loading of the precious metal iridium: PEM water electrolysis for hydrogen production involves low pH, high potential, and high anodic oxygen concentration. Iridium, the most corrosion-resistant metal in the catalyst layer, exhibits a low overpotential (0.32V-0.34V) in the OER (Oxygen Evolution Reaction) anode of PEM water electrolysis for hydrogen production, and is considered the best catalyst for PEM water electrolysis for hydrogen production. However, iridium is relatively rare on Earth, and high loadings of iridium are often required as catalysts in membrane electrode assemblies. Data shows that approximately 0.6 tons of iridium are needed to manufacture a 1GW PEM electrolyzer. 2. Constructing an efficient catalyst three-phase interface: The OER electrochemical reaction occurs at the three-phase reaction interface composed of a solid catalyst, pure water, and hydrogen / oxygen. This interface involves mass transfer processes between H2O molecules, intermediate groups, and gaseous products; charge transfer processes on the catalyst surface; and ion and electron conduction processes in the electrolyte, among others. Improvements are needed in the composition, structure, electrochemical processes, and reaction kinetics of the three-phase interface to enhance mass transfer efficiency and conductivity, thereby increasing the reaction efficiency of PEM water electrolysis. However, the current OER activity remains low.
[0004] Therefore, there is an urgent need to provide a new catalyst with high catalytic efficiency that can be used to improve OER activity. Summary of the Invention
[0005] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention proposes a composite multidimensional nanocatalyst, its preparation method, and its application. The composite multidimensional nanocatalyst has high catalytic efficiency and can be used to improve OER activity.
[0006] The first aspect of the present invention provides a composite multidimensional nanocatalyst.
[0007] Specifically, a composite multidimensional nanocatalyst, including IrO x and the load of the IrO x The carrier; The IrO x It has a core-shell structure, where x is greater than 0; The carrier is a polyaniline conductive polymer with a nanotube structure.
[0008] Preferably, the polyaniline conductive polymer is a semi-oxidized polyaniline conductive polymer.
[0009] Preferably, the IrO x It has an iridium oxide shell and an iridium metal core.
[0010] The composite multidimensional nanocatalyst is an OER catalyst and has the following advantages: 1. During the preparation of the composite multidimensional nanocatalyst, the diameter of the polyaniline conductive polymer nanotubes can be controlled by controlling the concentration of the aniline sulfate solution.
[0011] 2. Semi-oxidized polyaniline (PEM) exhibits high conductivity, which can accelerate the electron / ion conduction process; however, its conductivity is significantly affected by temperature, decreasing at high temperatures. The composite multidimensional nanocatalyst was prepared on nanotubes using both wet chemical and electrochemical oxidation methods to produce the catalytically active component IrO. x This avoids the influence of temperature on the conductivity of semi-oxidized polyaniline nanotubes.
[0012] 3. Semi-oxidized polyaniline conductive polymers have the advantage of acid corrosion resistance and are compatible with the low pH environment of water electrolysis for hydrogen production.
[0013] 4. The nanotube-structured polyaniline conductive polymer support possesses a three-dimensional usable surface, thereby exposing more active sites, effectively dispersing the nano-precious metal catalyst particles, inhibiting particle aggregation, and improving the specific activity of the composite multidimensional nanocatalyst. The structure of this nanotube-structured polyaniline conductive polymer support can promote mass transfer during the catalytic process.
[0014] 5. Core-shell structured IrO x The catalyst has an iridium oxide shell and an iridium metal core, and their synergistic effect can improve OER activity.
[0015] A second aspect of the present invention provides a method for preparing a composite multidimensional nanocatalyst.
[0016] Specifically, a method for preparing a composite multidimensional nanocatalyst includes the following steps: (1) The polystyrene (PS) fiber membrane is immersed in sulfuric acid solution for sulfonation treatment. The sulfonated polystyrene fiber membrane is taken out and placed in sulfuric acid aniline solution. An initiator is added and the reaction is carried out to obtain polyaniline / polystyrene nanocomposite fiber. The polyaniline / polystyrene nanocomposite fiber is then immersed in an organic solvent to obtain polyaniline nanotubes. (2) Preparation of iridium precursor solution: Mix surfactant, iridium salt and solvent to prepare iridium precursor solution; (3) The reducing agent, the polyaniline nanotubes, and the iridium precursor solution are mixed to prepare polyaniline conductive polymer-loaded Ir nano-metal material; (4) The surface of the Ir nano-metal in the polyaniline conductive polymer-supported Ir nano-metal material prepared in step (3) is oxidized to IrO by electrochemical oxidation. x Thus, the composite multidimensional nanocatalyst is obtained.
[0017] PS has easy modification properties; its surface can be sulfonated using concentrated sulfuric acid to introduce HSO3 into the PS surface. - The addition of functional groups allows aniline molecules to easily attach to PS fibers of different diameters. An initiator (such as ammonium persulfate) is then added to polymerize aniline at low temperatures, yielding a semi-oxidized polyaniline conductive polymer. The low solubility of polyaniline in organic solvents is then utilized to remove the PS fiber core, resulting in nanotube-shaped polyaniline conductive polymers of varying diameters. A reducing agent, polyaniline nanotubes, and an iridium precursor solution are mixed. Ir nanomaterials loaded onto the polyaniline conductive polymer are prepared in situ using a reducing agent (such as NaBH4). The surface of the loaded Ir nanomaterials is then oxidized to IrO via electrochemical oxidation. x Thus, the composite multidimensional nanocatalyst is obtained.
[0018] Preferably, in step (1), the polystyrene (PS) fiber membrane is prepared by electrospinning. By adjusting the concentration of the PS spinning solution, adding surfactants, and setting parameters such as the flow rate, temperature, humidity, spinning voltage, and distance between the spinning needle and the receiver in the spinning machine, the morphology and diameter of the PS fibers (nanoscale) are controlled to obtain uniform PS fibers, thereby obtaining a polystyrene (PS) fiber membrane.
[0019] Preferably, the preparation process of the polystyrene (PS) fiber membrane is as follows: PS particles are dissolved in DMF (N,N-dimethylformamide) with a PS volume concentration of 10-30%, heated until the PS is completely dissolved in DMF, cooled to room temperature, and TBAB (tetrabutylammonium bromide) surfactant is added and stirring is continued to obtain a spinning precursor solution; The spinning precursor solution is placed into a syringe, and the spinning machine's propulsion speed, temperature, humidity, distance between the spinning needle and the roller receiver, positive voltage, negative voltage, and roller speed are set to perform spinning to obtain a PS fiber membrane. This process can be repeated multiple times to prepare a sufficient quantity of PS fiber membranes.
[0020] Preferably, in step (1), the mass fraction of the sulfuric acid solution is greater than 90%, preferably 95-98%.
[0021] Preferably, in step (1), the sulfonation treatment temperature is 30-50℃, more preferably 40-45℃. The purpose of the sulfonation treatment is to enhance the adsorption of aniline cations.
[0022] Preferably, in step (1), the concentration of the aniline sulfate solution is 100-200 mmol / L, more preferably 160-180 mmol / L.
[0023] Preferably, in step (1), the initiator is ammonium persulfate or potassium persulfate.
[0024] Preferably, the concentration of the initiator is 100-200 mmol / L, more preferably 160-180 mmol / L.
[0025] Preferably, after adding the initiator, the reaction time is 15-24 hours, more preferably 20-24 hours. This reaction process involves low-temperature polymerization.
[0026] Preferably, in step (1), the organic solvent is tetrahydrofuran (THF). Immersing the polyaniline / polystyrene nanocomposite fibers in the organic solvent can remove the PS core, yielding polyaniline nanotubes.
[0027] Preferably, in step (2), the surfactant is hexadecyltrimethylammonium bromide (CTAB).
[0028] Preferably, in step (2), the iridium salt is selected from iridium halide, nitrate or sulfate, preferably IrCl3 or IrBr3.
[0029] Preferably, in step (2), the solvent is an alcohol, preferably ethanol.
[0030] Preferably, in step (2), the surfactant and iridium salt are first prepared into solutions, and then mixed.
[0031] Preferably, in step (2), the concentration of iridium salt in the iridium precursor solution is 0.5-5 mmol / L, preferably 1-2 mmol / L.
[0032] Preferably, in step (3), the reducing agent is a strong reducing agent, such as sodium borohydride (NaBH4).
[0033] Preferably, in step (3), the polyaniline nanotubes are added in the form of a colloidal solution. The preparation process of the colloidal solution is as follows: the polyaniline nanotubes prepared in step (1) are dried, then ethanol is added, and the solution is ultrasonically vibrated and stirred in an ice-water bath to obtain the colloidal solution.
[0034] Preferably, in step (4), the Ir nano-metal material loaded on the polyaniline conductive polymer in step (3) is dried, and then mixed with ultrapure water, isopropanol, and Nafion (perfluorosulfonic acid-based polymer), and ultrasonically dispersed to obtain catalyst ink. The catalyst ink is then transferred to a glassy carbon electrode and dried in a drying oven. Afterward, the catalyst is electrochemically cycled to +1.5 to +1.7V using an electrochemical workstation (this process involves electrochemical oxidation). The powder on the glassy carbon electrode is then removed, which is the composite multidimensional nano-catalyst.
[0035] A third aspect of the present invention provides a membrane electrode.
[0036] A membrane electrode comprising the above-mentioned composite multidimensional nanocatalyst.
[0037] A method for preparing a membrane electrode includes the following steps: The composite multidimensional nanocatalyst was dispersed and mixed with water, alcohol, and ionomer solutions in an ice-water bath to obtain a slurry. The slurry was transferred to a proton exchange membrane using a doctor blade coating method and a transfer method. The wettability of the catalyst slurry was controlled by different dispersions, and the loading of the composite multidimensional nanocatalyst was controlled by the thickness of the doctor blade coating. Finally, the membrane electrode was formed.
[0038] Compared with the prior art, the beneficial effects of the present invention are as follows: The composite multidimensional nanocatalyst of this invention effectively disperses nano-noble metal catalyst particles, inhibits particle aggregation, and thus improves the mass-to-specific activity of the composite multidimensional nanocatalyst. The nanotube-structured polyaniline conductive polymer support promotes mass transfer during the catalytic process. The core-shell structure of IrO... x The catalyst has an iridium oxide shell and an iridium metal core, and their synergistic effect can improve OER activity. Attached Figure Description
[0039] Figure 1 This is a SEM image of the polystyrene (PS) fiber membrane used in the preparation process of the composite multidimensional nanocatalyst in Example 1 of the present invention. Figure 2 The images show SEM images of the composite multidimensional nanocatalysts prepared in Examples 1-4 of this invention. Detailed Implementation
[0040] To enable those skilled in the art to more clearly understand the technical solutions described in this invention, the following embodiments are provided for illustration. It should be noted that the following embodiments do not constitute a limitation on the scope of protection claimed by this invention.
[0041] Unless otherwise specified, the raw materials, reagents or devices used in the following examples are available from conventional commercial sources or can be obtained by existing known methods.
[0042] Example 1: Preparation of composite multidimensional nanocatalysts and membrane electrodes A composite multidimensional nanocatalyst comprising IrO x and load IrO x The carrier; IrO x It has a core-shell structure, where x is greater than 0; The carrier is a polyaniline conductive polymer with a nanotube structure; IrO x It has an iridium oxide shell and an iridium metal core.
[0043] A method for preparing a composite multidimensional nanocatalyst includes the following steps: (1) Preparation of polystyrene spinning precursor solution: Dissolve 20g of PS particles with a molecular weight of 280,000 into 100mL of DMF (N,N-dimethylformamide) solution, with a PS volume concentration of 20%. Stir magnetically at 60℃ until the PS particles are completely dissolved in DMF. After the solution cools to room temperature of 25℃, add 0.2g of TBAB (tetrabutylammonium bromide) surfactant and continue stirring for 12 hours until the PS particles are completely dissolved to obtain the spinning precursor solution; (2) Place 5 mL of spinning precursor solution into a syringe, set the spinning machine flow rate to 0.5 mL / h, the spinning machine temperature to 30℃, the humidity to 30%, the distance between the spinning needle and the roller receiver to 12 cm, the positive voltage to 15 KV, the negative voltage to -2.5 KV, and the roller speed to 30 rpm. After spinning for 6 hours, polystyrene (PS) fiber membrane is obtained. This process can be repeated multiple times to prepare a sufficient amount of polystyrene (PS) fiber membrane. (3) After the spinning machine has finished spinning, remove the aluminum foil with the polystyrene (PS) fiber membrane, immerse the polystyrene (PS) fiber membrane in 98% concentrated sulfuric acid for 6 hours, and set the reaction temperature to 40℃ to obtain sulfonated polystyrene fiber membrane. Clean the sulfonated polystyrene fiber membrane with ultrapure water, and then place it in a 180 mmol / L aniline sulfuric acid solution (aniline sulfuric acid solution is aniline dissolved in 1 mol / L dilute sulfuric acid, and the concentration of aniline is 180 mmol / L) for 12 hours. Aniline cations are adsorbed onto the surface of PS fibers, and then a 180 mmol / L ammonium persulfate solution is slowly added dropwise. The reaction is carried out at 5°C for 24 hours to obtain polyaniline / polystyrene nanocomposite fibers. The polyaniline / polystyrene nanocomposite fibers are washed three times with pure water and ethanol, and then soaked in THF (tetrahydrofuran) for 24 hours to remove the PS core, resulting in polyaniline nanotubes. Excess THF is washed away with ultrapure water and ethanol, and the nanotubes are placed in a vacuum drying oven and dried at 60°C for 24 hours for later use. (4) Preparation of IrCl3 precursor solution: Dissolve 5.625g cetyltrimethylammonium bromide (CTAB) and 0.448g iridium chloride (IrCl3) in 270mL and 112.5mL of ethanol, respectively. Then, sonicate each solution for 10 minutes and mix them with a magnetic stirrer at 500rpm for 30 minutes. Mix the two solutions together. The concentration of IrCl3 is about 1mmol / L. (5) Preparation of polyaniline nanotube colloidal solution: 100 mg of polyaniline nanotube powder was added to 100 mL of ethanol, and ultrasonic vibration was performed for 15 minutes in an ice water bath. Then, the mixture was stirred for 15 minutes to obtain polyaniline nanotube colloidal solution. (6) With the aid of an ultrasonic bath, 0.684 g of sodium borohydride (NaBH4) was placed in 45 mL of ethanol (this is 1 part), and the mixture was vibrated until NaBH4 was completely dissolved. Five parts of the above reducing agent were added to the IrCl3 precursor solution in step (4) at a speed of 2 mL / min, and the polyaniline nanotube colloidal solution in step (5) was added. The mixture was stirred at a speed of 600 rpm. The synthesized particles were then centrifuged at 8000 rpm for 5 minutes to separate the polyaniline conductive polymer loaded with Ir nano metals from the liquid phase. In order to remove contaminants, the polyaniline conductive polymer loaded with Ir nano metals was washed four times with ethanol and deionized water, and then dried in a vacuum drying oven at 40°C for later use. (7) Add 100 mg of the polyaniline conductive polymer-supported Ir nano-metal powder prepared in step (6) to 5 mL of ultrapure water and 5 mL of isopropanol, then add 2 mL of 5 wt% Nafion solution, and disperse the mixture by using an ultrasonic vibration system for 15 minutes to obtain a uniform catalyst ink. Transfer the catalyst ink to a glassy carbon electrode and dry it in a drying oven at 60 °C for 10 minutes. Then, use an electrochemical workstation to perform electrochemical cycling on the catalyst on the glassy carbon electrode to +1.7 V (this process is electrochemical oxidation) to obtain the composite multidimensional nano-catalyst.
[0044] The fabrication of a membrane electrode includes the following steps: A water-alcohol mixture was prepared by mixing deionized water and isopropanol in a 1:1 ratio. The aforementioned composite multidimensional nanocatalyst and 5 wt% Nafion solution were then added to obtain a slurry. The composite multidimensional nanocatalyst comprised 20 wt% of the total slurry, and the mass ratio of the 5 wt% Nafion solution to the composite multidimensional nanocatalyst was 6:1. The slurry was ultrasonically dispersed in an ice-water bath for 30 min. 200 μL of the slurry was placed on a PTFE (polytetrafluoroethylene) substrate, and then dispersed at 2 cm·s⁻¹. -1 The coating is applied using a moving doctor blade. After electrochemical oxidation of the slurry, the gap between the doctor blade and the substrate is adjusted to 150 μm on a vacuum coating machine, and the coating width is set to 8 cm. After coating, it is dried in a ventilated drying oven at 80°C to form a coating. The Nafion 117 film is then sequentially coated with 5 wt% H2O2 solution, distilled water, and 0.5 mol·L⁻¹ solution. -1 The PTFE substrate was pretreated with H2SO4 solution and distilled water (80℃). The coating was then transferred from the PTFE substrate to the pretreated Nafion 117 film via hot-pressing. Hot-pressing was then performed at 135℃ and 75 kg·cm². -2 The process was carried out for 3 minutes under the specified conditions, and finally the membrane electrode (which can be called CCM membrane electrode) was obtained.
[0045] Example 2 A method for preparing a composite multidimensional nanocatalyst includes the following steps: Steps (1), (2), and (3) are the same as in Example 1; Step (4) Preparation of IrCl3 precursor solution: Dissolve 5.625g cetyltrimethylammonium bromide (CTAB) and 0.571g iridium chloride (IrCl3) in 270mL and 112.5mL of ethanol, respectively. Then, sonicate each solution for 10 minutes and mix them with a magnetic stirrer at 500rpm for 30 minutes. Mix the two solutions together. The concentration of IrCl3 is 5mmol / L. Step (5) is the same as in Example 1; Step (6): The sodium borohydride ratio was changed as follows to completely reduce IrCl3: With the aid of an ultrasonic bath, 1.368g of sodium borohydride (NaBH4) was placed in 45ml of ethanol (this is 1 part), and the mixture was vibrated until NaBH4 was completely dissolved. Five parts of the above reducing agent were added to the IrCl3 precursor solution in step (4) at a speed of 2mL / min, and the polyaniline nanotube colloidal solution in step (5) was added. The mixture was stirred at a speed of 600rpm, and then the synthesized particles were centrifuged at 8000rpm for 5 minutes to separate the polyaniline conductive polymer loaded with Ir nano-metal from the liquid phase. In order to remove contaminants, the polyaniline conductive polymer loaded with Ir nano-metal was washed four times with ethanol and deionized water, and then dried in a vacuum drying oven at 40℃ for later use. The remaining steps are the same as in Example 1.
[0046] The preparation process of the membrane electrode is the same as that in Example 1, except that the composite multidimensional nanocatalyst prepared in this example is used instead of the composite multidimensional nanocatalyst prepared in Example 1.
[0047] Example 3 A method for preparing a composite multidimensional nanocatalyst includes the following steps: Steps (1), (2), and (3) are the same as in Example 1; Step (4) Preparation of IrCl3 precursor solution: Dissolve 5.625g cetyltrimethylammonium bromide (CTAB) and 1.142g iridium chloride (IrCl3) in 270mL and 112.5mL of ethanol, respectively. Then, sonicate each solution for 10 minutes and mix them with a magnetic stirrer at 500rpm for 30 minutes. Mix the two solutions together. The concentration of IrCl3 is 10mmol / L. Step (5) is the same as in Example 1; Step (6): The sodium borohydride ratio was changed as follows to completely reduce IrCl3: With the aid of an ultrasonic bath, 2.736 g of sodium borohydride (NaBH4) was placed in 90 mL of ethanol (this is 1 part), and the mixture was vibrated until NaBH4 was completely dissolved. Five parts of the above reducing agent were added to the IrCl3 precursor solution in step (4) at a speed of 2 mL / min, and the polyaniline nanotube colloidal solution in step (5) was added. The mixture was stirred at a speed of 600 rpm, and then the synthesized particles were centrifuged at 8000 rpm for 5 minutes to separate the polyaniline conductive polymer loaded with Ir nano-metal from the liquid phase. In order to remove contaminants, the polyaniline conductive polymer loaded with Ir nano-metal was washed four times with ethanol and deionized water, and then dried in a vacuum drying oven at 40°C for later use. The remaining steps are the same as in Example 1.
[0048] The preparation process of the membrane electrode is the same as that in Example 1, except that the composite multidimensional nanocatalyst prepared in this example is used instead of the composite multidimensional nanocatalyst prepared in Example 1.
[0049] Example 4 A method for preparing a composite multidimensional nanocatalyst includes the following steps: Steps (1), (2), and (3) are the same as in Example 1; Step (4) Preparation of IrCl3 precursor solution: Dissolve 5.625g cetyltrimethylammonium bromide (CTAB) and 2.855g iridium chloride (IrCl3) in 270mL and 112.5mL of ethanol, respectively. Then, sonicate each solution for 10 minutes and mix them with a magnetic stirrer at 500rpm for 30 minutes. Mix the two solutions together. The concentration of IrCl3 is 25mmol / L. Step (5) is the same as in Example 1; Step (6): The sodium borohydride ratio was changed as follows to completely reduce IrCl3: With the aid of an ultrasonic bath, 3.9g of sodium borohydride (NaBH4) was placed in 100ml of ethanol (this is 1 part), and the mixture was vibrated until NaBH4 was completely dissolved. Five parts of the above reducing agent were added to the IrCl3 precursor solution in step (4) at a speed of 2mL / min, and the polyaniline nanotube colloidal solution in step (5) was added. The mixture was stirred at a speed of 600rpm, and then the synthesized particles were centrifuged at 8000rpm for 5 minutes to separate the polyaniline conductive polymer loaded with Ir nano-metal from the liquid phase. In order to remove contaminants, the polyaniline conductive polymer loaded with Ir nano-metal was washed four times with ethanol and deionized water, and then dried in a vacuum drying oven at 40℃ for later use. The remaining steps are the same as in Example 1.
[0050] The preparation process of the membrane electrode is the same as that in Example 1, except that the composite multidimensional nanocatalyst prepared in this example is used instead of the composite multidimensional nanocatalyst prepared in Example 1.
[0051] Comparative Example 1 Compared to Example 1, Comparative Example 1 differs in that the IrOx core-shell structure catalyst (i.e., the catalyst does not contain a nanotube structure in the polyaniline conductive polymer) was prepared in Comparative Example 1. Specifically, no polyaniline nanotube colloidal solution was added during the IrCl3 reduction step; the remaining preparation process was the same as in Example 1.
[0052] Comparative Example 2 Compared with Example 1, in the preparation process of the membrane electrode in Comparative Example 2, commercial iridium black was used instead of the composite multidimensional nanocatalyst in Example 1, and the rest of the preparation process was the same as that of the membrane electrode in Example 1.
[0053] Comparative Example 3 A method for preparing a composite multidimensional nanocatalyst includes the following steps: Steps (1) and (2) are the same as in Example 3; Step (3): After the spinning machine completes the process, remove the aluminum foil with the polystyrene (PS) fiber membrane. Immerse the polystyrene (PS) fiber membrane in 98% concentrated sulfuric acid for 6 hours. Set the reaction temperature to 40℃ to obtain a sulfonated polystyrene fiber membrane. Clean the sulfonated polystyrene fiber membrane with ultrapure water, and then place it in a 180 mmol / L pyrrole sulfuric acid solution (pyrrole is dissolved in 1 mol / L dilute sulfuric acid solution, and the concentration of pyrrole is 180 mmol / L) for 12 hours to allow pyrrole cations to adsorb onto the PS fiber surface. Then, slowly add 180 mmol / L ammonium persulfate solution and react at a low temperature of 5℃ for 24 hours to obtain polypyrrole / PS nanocomposite fibers. Wash the polypyrrole / PS nanocomposite fibers with pure water and ethanol three times, and then immerse them in THF for 24 hours to remove the PS core, obtaining polypyrrole nanotubes. Wash off excess THF with ultrapure water and ethanol, and place them in a vacuum drying oven to dry at 60℃ for 24 hours for later use.
[0054] The remaining steps are the same as in Example 3.
[0055] The preparation process of the membrane electrode is the same as that in Example 3, except that the composite multidimensional nanocatalyst prepared in this comparative example is used instead of the composite multidimensional nanocatalyst prepared in Example 3.
[0056] Product effectiveness test 1. Figure 1 This is a SEM image of the polystyrene (PS) fiber membrane used in the preparation process of the composite multidimensional nanocatalyst in Example 1 of the present invention. Figure 2 The images show SEM images of the composite multidimensional nanocatalysts prepared in Examples 1-4 of this invention.
[0057] Figure 2 In the diagram, “A” corresponds to the SEM image of the composite multidimensional nanocatalyst of Example 1, “B” corresponds to the SEM image of the composite multidimensional nanocatalyst of Example 2, “C” corresponds to the SEM image of the composite multidimensional nanocatalyst of Example 3, and “D” corresponds to the SEM image of the composite multidimensional nanocatalyst of Example 4.
[0058] 2. Catalytic activity and membrane electrode performance testing Catalyst testing process: First, the catalyst ink was prepared. The catalyst powder prepared in the examples and comparative examples was prepared as follows: 2-5 mg of catalyst powder was added to 2.5 mL of ultrapure water and 2.5 mL of isopropanol, and then 20 μL of 5 wt% Nafion solution was added. The catalyst was dispersed by using an ultrasonic vibration system for 15 minutes to obtain a uniform catalyst ink.
[0059] Use a pipette to transfer 10 μL of catalyst ink onto a pre-polished and cleaned glassy carbon rotating disk electrode, and air dry it in a drying oven at 30 degrees Celsius.
[0060] A three-electrode system consisting of a rotating disk electrode, a platinum wire electrode, and a saturated Ag / AgCl electrode was used. A series of cyclic voltammetry (CV) scans were performed at different scan rates, ranging from 0 to +1.7 V, using an electrochemical workstation. Electrochemical impedance spectroscopy (EIS) measurements were also conducted in the range of 1 Hz–1000 kHz with a perturbation voltage of 5 mV.
[0061] ADT durability testing was performed on the catalyst: FTO conductive glass (as the working electrode) was coated with catalyst ink for ADT testing. ADT refers to 1000 voltage cycles of 1.2V to 1.7V vs RHE, with a scan rate of 100 mV / s. The CV curves were then compared.
[0062] Membrane electrode testing process: 1. The catalyst loading is obtained by balancing the mass of catalyst used during coating.
[0063] 2. The membrane electrode is mounted in the electrolytic cell fixture, and a two-electrode system is used to perform CV scanning of the electrolytic cell to obtain the polarization curve. The potentials corresponding to the current densities in Table 2 are then obtained based on the polarization curves.
[0064] Table 1: Catalytic activity results
[0065] Table 2: Membrane Electrode Performance
[0066] Tables 1 and 2 present the electrochemical characterization results of the composite multidimensional nanocatalysts in the examples and comparative examples, as well as the performance of the membrane electrode in the electrolytic cell fixture. It can be seen that the composite multidimensional nanocatalyst in Example 3 has the highest mass activity, the lowest Rs impedance and Rct impedance, and the lowest performance loss. This indicates that Example 3 has better electron / ion transport characteristics and charge transfer characteristics in OER. The relatively low activity in Examples 1 and 2 can be attributed to insufficient Ir metal loading. Although Example 4 has a larger Ir nanometal loading, the metal agglomerates on the nanotube surface, leading to a decrease in its activity. Compared to Comparative Example 1, Example 3 has lower Rs and Rct, indicating that the polyaniline conductive polymer nanotubes effectively increase the catalyst's conductivity and activity in the Faraday electrochemical region. Compared to Comparative Example 2, Example 3 has three times the mass activity of a commercial iridium black catalyst. Compared to Comparative Example 3, Example 3 exhibits higher OER performance and durability than the composite catalyst using polypyrrole conductive polymer as a support.
[0067] The above comparison demonstrates that the nanotube-structured polyaniline conductive polymer, used as a support, enables the catalyst to exhibit higher proton and electron transport efficiency, thereby enhancing the durability of the catalyst particles to some extent. Meanwhile, Example 3 in Table 2 achieves 1 A / cm²... 2 and 2A / cm 2 It exhibits a low overpotential. This further demonstrates that the polyaniline conductive polymer with a nanotube structure, as a catalyst support, can reduce the overpotential and achieve better PEM electrolysis water performance.
[0068] In summary, the ratio of nano-iridium metal and conductive polymer support in Example 3 is reasonable, and the composite multidimensional nanocatalyst exhibits good dispersion morphology. Furthermore, polyaniline is more suitable for the working environment of PEM water electrolysis compared to polypyrrole.
Claims
1. A composite multidimensional nanocatalyst, characterized in that, Including IrO x and the load of the IrO x The carrier; The IrO x It has a core-shell structure, where x is greater than 0; the IrO x It has an iridium oxide shell and an iridium metal core; The carrier is a polyaniline conductive polymer with a nanotube structure, and the polyaniline conductive polymer is a semi-oxidized polyaniline conductive polymer. The composite multidimensional nanocatalyst is prepared by a method including the following steps: (1) The polystyrene fiber membrane is immersed in sulfuric acid solution for sulfonation treatment. The sulfonated polystyrene fiber membrane is taken out and placed in sulfuric acid aniline solution. An initiator is added and the reaction is carried out to obtain polyaniline / polystyrene nanocomposite fiber. The polyaniline / polystyrene nanocomposite fiber is then immersed in an organic solvent to obtain polyaniline nanotubes. (2) Preparation of iridium precursor solution: Mix surfactant, iridium salt and solvent to prepare iridium precursor solution; (3) The reducing agent, the polyaniline nanotubes, and the iridium precursor solution are mixed to prepare polyaniline conductive polymer-loaded Ir nano-metal material; (4) The surface of the Ir nano-metal in the polyaniline conductive polymer-supported Ir nano-metal material prepared in step (3) is oxidized to IrO by electrochemical oxidation. x Thus, the composite multidimensional nanocatalyst is obtained.
2. The composite multidimensional nanocatalyst according to claim 1, characterized in that, The preparation process of the polystyrene fiber membrane is as follows: PS particles are dissolved in N,N-dimethylformamide, the volume concentration of polystyrene is 10-30%, the mixture is heated until the polystyrene is completely dissolved, the temperature is lowered, tetrabutylammonium bromide surfactant is added and stirring is continued to obtain the spinning precursor solution; The spinning precursor liquid is placed into a syringe, and the spinning machine's propulsion speed, temperature, humidity, distance between the spinning needle and the roller receiver, positive voltage, negative voltage, and roller speed are set to perform spinning and obtain a polystyrene fiber membrane.
3. The composite multidimensional nanocatalyst according to claim 1, characterized in that, In step (1), the mass fraction of the sulfuric acid solution is greater than 90%; in step (1), the sulfonation treatment temperature is 30-50℃.
4. The composite multidimensional nanocatalyst according to claim 1, characterized in that, In step (1), the concentration of the aniline sulfate solution is 100-200 mmol / L; after adding the initiator, the reaction time is 15-24 hours.
5. The composite multidimensional nanocatalyst according to claim 1, characterized in that, In step (2), the surfactant is hexadecyltrimethylammonium bromide; in step (2), the iridium salt is selected from iridium halide, nitrate or sulfate; in step (2), the concentration of iridium salt in the iridium precursor solution is 0.5-5 mmol / L.
6. The composite multidimensional nanocatalyst according to claim 1, characterized in that, In step (4), the Ir nano-metal material loaded on the polyaniline conductive polymer in step (3) is dried, and then mixed with ultrapure water, isopropanol, and perfluorosulfonic acid-based polymer, and ultrasonically dispersed to obtain catalyst ink; the catalyst ink is transferred to a glassy carbon electrode, dried, and the catalyst is electrochemically cycled to +1.5 to +1.7V using an electrochemical workstation, and the powder on the glassy carbon electrode is removed, which is the composite multidimensional nano-catalyst.
7. A membrane electrode, characterized in that, Including the composite multidimensional nanocatalyst according to any one of claims 1-6.
Citation Information
Patent Citations
Preparation method of supported catalyst for PEM electrolyzed water
CN114657577A
